A Fundamental Fear - Anas Malik (International Institute of Islamic Thought, 2005)
A Fundamental Fear: Eurocentrism and the Emergence of Islamism uses critical theory to examine the Islamists’ political projects and their depictions. Scholars are divided between those who believe in a religious or national essence to the Muslim community (essentialists) and those who reject this assumption (anti-essentialists). In regards to a Muslim essence, Sayyid identifies two existing scholarly camps: Orientalists assume an ahistorical, acontextual Islamic essence that drives and shapes Muslim society and activity through most places and ages. Anti-Orientalists, as manifested in such writers as Hamid El-Zien, assert that there is not one “Islam,” but only many “Islams.” According to this view, Islam and indeed all religion cannot exist as an analytic category having a self-sustaining, positive, fixing, universal, and autonomous content; rather, religion is only manifested through particular contexts. While acknowledging an intellectual debt to Edward Said, whose critiques fed the anti-Orientalist camp, Sayyid argues for a middle path between Orientalist and anti-Orientalist understandings. Orientalists claim that the relationship between Islam and Islamism is direct, whereas anti- Orientalists claim that the relationship is merely opportunistic – Islam is what Marxists might call “superstructural” (a surface action over deeper, more real material contests) and is driven by a false consciousness. Picking theoretical fruit from writers who explored signs, ideas, and language, among them Slavoj Zizek, Roland Barthes, and Jacques Lacan, the author asks Zizek’s general question: “What creates and sustains the identity of a given ideological field beyond all possible variations of its ideological content?” (p. 44). Analysts typically find themselves unable to answer this question without reasserting a new Orientalism. Sayyid asserts that despite the malleability of Islamic symbols and Islamist programs, Islam has retained its specificity, a term by which he means the traces of its original meaning articulated at the foundation, traces that have been invoked repeatedly. Islam is a crucial nodal point, à la Jacques Lacan, retrospectively giving meaning to other elements, be they Sufi discussions, debates on fiqh, or other discourses (p. 45) ...